High Incubation Attendance and Nesting Site Constraints of the Sclater's Monal in an Alpine Environment in Southwestern China - Nehafta Bibi; Ge Gao; Dan Liang; Xu Luo (Ecology and Evolution)
ABSTRACT Breeding in alpine environments poses significant challenges to birds, requiring specific adaptations for survival. The Sclater's monal (Lophophorus sclateri), a regionally threatened, typical alpine pheasant species, is restricted to high‐elevation habitat from the East Himalayas to the mountains of west Yunnan, China. Due to its low population density and the difficulty of accessing its habitats, the breeding ecology of this species is understudied. Therefore, we aimed to understand the breeding behavior, nest site use, and life‐history traits that allow this monal species to cope with the alpine environment. During our fieldwork from March to June 2015 and 2016 in the Gaoligong Mountains in western Yunnan, China, we found six cliff nesting sites ranging from 3535 m to 3892 m. Three sites were active, with one being used in both years, and the remaining three were inactive but had been used in prior years. The clutch size was 2.75 ± 0.5 (2 or 3 eggs; n = 4 nests at three nesting sites), and all 11 eggs were successfully hatched. The female solely performed incubation, spending 97.2% of its time in incubating with an average duration of 25.69 ± 13.79 h (n = 43 bouts across three females) per on‐bout which indicates the female bird invested more time than other pheasants. High incubation attendance by females highlights the importance of increased parental care in ensuring reproductive success. These findings highlight that the Sclater monal exhibits specific breeding behaviors and nesting strategies that reflect adaption to harsh environments. Additionally, our observations of intense male–male interactions and reuse of nesting sites suggest that suitable nesting sites are limited, which could significantly impact population dynamics. Together, these insights are crucial for conserving this regionally threatened pheasant.